Should I Lay or Should I Grow: Photoperiodic Versus Metabolic Cues in Chickens - Hanlon, Charlene; Ramachandran, Ramesh; Zuidhof, Martin J.; Bédécarrats, Grégoy Y. (Frontiers in Physiology, 2020)
While photoperiod has been generally accepted as the primary if not the exclusive cue to stimulate reproduction in photoperiodic breeders such as the laying hen, current knowledge suggests that metabolism and/or body composition can also play an influential role to control the hypothalamic-pituitary gonadal (HPG)-axis. This review thus intends to first describe how photoperiodic and metabolic cues can impact the HPG axis, then explore and propose potential common pathways and mechanisms through which both cues could be integrated. Photostimulation refers to a perceived increase in day-length resulting in the stimulation of the HPG. While photoreceptors are present in the retina of the eye and the pineal gland, it is the deep brain photoreceptors (DBPs) located in the hypothalamus that have been identified as the potential mediators of photostimulation, including melanopsin (OPN4), neuropsin (OPN5), and vertebrate-ancient opsin (VA-Opsin). Here, we present the current state of knowledge surrounding these DBPs, along with their individual and relative importance and, their possible downstream mechanisms of action to initiate the activation of the HPG. On the metabolic side, specific attention is placed on the hypothalamic integration of appetite control with the stimulatory (Gonadotropin Releasing Hormone; GnRH) and inhibitory (Gonadotropin Inhibitory Hormone; GnIH) neuropeptides involved in the control of the HPG axis. Specifically, the impact of orexigenic peptides agouti-related peptide (AgRP) and neuropeptide Y (NPY), as well as the anorexigenic peptides pro-opiomelanocortin (POMC) and cocaine-and amphetamine regulated transcript (CART) is reviewed. Furthermore, beyond hypothalamic control, several metabolic factors involved in the control of body weight and composition are also presented as possible modulators of reproduction at all three levels of the HPG axis. These include peroxisome proliferator-activated receptor gamma (PPAR-) for its impact in liver metabolism during the switch from growth to reproduction, adiponectin as a potential modulator of ovarian development and follicular maturation, as well as growth hormone (GH) and leptin (LEP).